Leadership and Creativity in Public Services: An Interview With Lord Michael Bichard, Chair of the National Audit Office. (January 2018) - Bolden, Richard; O'Regan, Nicholas
This interview with Lord Michael Bichard, one of the most distinguished public sector leaders in the United Kingdom, explores his ideas around the relationship between leadership, creativity, and innovation. A champion of place-based approaches to public services, where citizens are actively involved in service design, delivery, and appraisal, Bichard advocates the need for inclusive and supportive leadership that enables the emergence of the kinds of creativity required to respond to the financial challenges facing the public sector. Bichard's ideas resonate with recent research on creative leadership and provide a practical illustration of place-based and systems leadership in the public sector and beyond.